Aksara Arab-Melayu di Nusantara dan Sumbangsihnya dalam Pengembangan Khazanah Intelektual - Ellya Roza (Universitas Darussalam Gontor, 2017)
Literacy is a tool of communication which could help people to know the natural surroundings without any real experience, but they could know the events of the past. As a relic, the literacy cannot be ignored. For example, the literacy of Arabic-Malay is a tool to write Malay language for the people who live in the archipelago. With the help of the Arab-Malay literacy, Moslem sholars, kiais, and teachers are able to produce real works that characterizes the traditional writing of citizens. The works of the past people implemented in Arabic-Malay and Malay are called Malay manuscripts. The number of Malay manuscripts is innumerable and has been saved by 28 countries in the world. The Malay manuscripts will not contribute to society nowadays if they are not read and the people do not understand their contents. Therefore, it is important to do a research for the existence of the Arab-Malay literacy in the archipelago. Moreover, the deep research is needed to know its role to read the Malay manuscripts which are ones of the intellectual treasures of the archipelago till the manuscripts can be understood by the people now. It is very necessary to do because the Arab-Malay literacy as a part of the archipelago culture has been